Experimental and numerical assessment of steel beams under impact loadings. (July 2019) - D'Antimo, M.; Latour, M.; Rizzano, G.; Demonceau, J.F.
Abstract: In order to provide a contribution towards a better understanding of the physical phenomena involved in the design of steel structures under impacts, the present paper focuses on the behaviour of simply supported beams in drop-weight tests analysing the possibility to model the response numerically through the FE approach. These tests represent an important benchmark to study the behaviour of steel members under impacts and they are usually necessary to provide an accurate modelling of structures under exceptional loading conditions. In the present study, nine experimental tests were conducted on simply supported beams analysing the response of members under the application of increasing weights and dropping heights. Subsequently, in order to evaluate the capabilities of the currently available FE modelling techniques a numerical model was calibrated in Abaqus/CAE verifying its accuracy against the experimental results. Different techniques and material constitutive laws were investigated with the aim to define the most appropriate modelling approach to account for strain rate effects. The numerical results were compared with the experimental ones, demonstrating that, when the strain rate effect is accounted for adequately in the material stress-strain law, the FE modelling is a valid tool to predict the response of steel beams under impact loads. Among the models considered, the Johnson-Cook and Cowper-Symonds constitutive laws provided the best accuracy in terms of peak displacement, peak force and residual displacement. Highlights: The results of drop-weight tests on steel beams are presented. The Dynamic Increase Factors for steel beams into an impact loading scenario are evaluated. A FE model of the steel beams is developed in a dynamic implicit framework. The influence of strain rate in the FE modelling is assessed. The capabilities of different materials constitutive laws are evaluated.